Effects of Radiation on Materials: Sixteenth International Symposium 1994
DOI: 10.1520/stp23945s
|View full text |Cite
|
Sign up to set email alerts
|

The Radiation Hardening and Embrittlement of a Mild Steel Submerged-Arc Weld

Abstract: This paper provides details of accelerated irradiation experiments on a Magnox mild steel submerged-arc weld at mean irradiation temperatures of 165°C and 269°C. The irradiation-induced changes in mechanical properties and weld microstructure have been determined. Irradiation increased the 40J transition temperature and the yield stress. The increase in transition temperature at a given dose was rather higher in the lower temperature irradiations. Irradiation-induced precipitates of about 2nm diameter were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Phosphorus is one of the major causes of embrittlement of nuclear reactor pressure vessel (RPV) steels [1]. A huge enhancement of the concentration of phosphorus (P) atoms at grain boundaries is observed in samples of RPV steels taken from nuclear reactors [2]. This leads to a decrease in the grain boundary cohesion and consequently to a shift of the ductile-to-brittle transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus is one of the major causes of embrittlement of nuclear reactor pressure vessel (RPV) steels [1]. A huge enhancement of the concentration of phosphorus (P) atoms at grain boundaries is observed in samples of RPV steels taken from nuclear reactors [2]. This leads to a decrease in the grain boundary cohesion and consequently to a shift of the ductile-to-brittle transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that grain boundary segregation of phosphorous was observed after re-irradiation of previously irradiated weld surveillance specimens in the Magnox reactors in the UK. 2,3) A remarkable grain boundary phosphorous segregation was also observed in the weld of the pressure vessel of Russian VVER. 4,5) Therefore, several studies on the effects of phosphorus segregation on intergranular fracture 6,7) and on the segregation modeling [8][9][10] have been carried out.…”
Section: Introductionmentioning
confidence: 86%
“…Next, the interaction with dislocation lines of dislocation loops has been studied for different solute concentrations by Terentyev et al [5], concluding that Mn segregated in the core of loops causes an increment in the yield point and finally increases the hardening. P is also known to segregate to heterogeneities in RPV steels, mainly grain boundaries and dislocations, causing embrittlement, grain boundary decohesion and thereupon a shift in the ductile-to-brittle transition temperature [6][7].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…One sample with a dipole of edge dislocations is generated using linear elasticity [12] in a crystallite with the normal axes x, y and z oriented as the [ , where a 0 is the lattice parameter of Fe [4][5][6][7][8][9][10][11][12][13].…”
Section: Thermodynamic Modelling With the Md-mc Techniquementioning
confidence: 99%